2022
DOI: 10.1021/acs.molpharmaceut.1c00926
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Link between Pancratistatin and Mitochondrial Apoptosis through Changes in the Membrane Dynamics on the Nanoscale

Abstract: Pancratistatin (PST) is a natural antiviral alkaloid that has demonstrated specificity toward cancerous cells and explicitly targets the mitochondria. PST initiates apoptosis while leaving healthy, noncancerous cells unscathed. However, the manner by which PST induces apoptosis remains elusive and impedes the advancement of PST as a natural anticancer therapeutic agent. Herein, we use neutron spin−echo (NSE) spectroscopy, molecular dynamics (MD) simulations, and supporting small angle scattering techniques to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…Using NSE we are able to look at the bending modulus (κ), which sheds light on the elastic properties of the bilayer system in question. 56,57 Elastic properties have been reported to have significance in biological processes, such as budding, formation of stalks, and adsorption, all of which are relevant to the functionality of PS. 58,59 Our results suggest that the incorporation of MCT had an overall softening effect on the lipid-only bilayers.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using NSE we are able to look at the bending modulus (κ), which sheds light on the elastic properties of the bilayer system in question. 56,57 Elastic properties have been reported to have significance in biological processes, such as budding, formation of stalks, and adsorption, all of which are relevant to the functionality of PS. 58,59 Our results suggest that the incorporation of MCT had an overall softening effect on the lipid-only bilayers.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Although generally described as a monolayer system, pulmonary surfactant also forms multilayers that are referred to as surfactant reservoirs. ,, These bilayers tend to form upon compression of the monolayer, which causes buckling of the film, leading to bilayer folds protruding into the water subphase of the air–water interface. Using NSE we are able to look at the bending modulus (κ), which sheds light on the elastic properties of the bilayer system in question. , Elastic properties have been reported to have significance in biological processes, such as budding, formation of stalks, and adsorption, all of which are relevant to the functionality of PS. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, pancratistatin has been proved to selectively induce apoptosis of a variety of human cancer cells, but has no significant effect on non-cancer cells [10]. Natasha Kekre studied human lymphoma cells (Jurkat), and found that pancratistatin in Jurkat cells caused early activation of caspase-3 and reversal of phosphatidylserine, and induced cancer cells to use non genomic target cells to apoptosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…This scheme exploits the sensitivity of SANS between hydrogen and deuterium, allowing the time-dependent mixing to be tracked. It has been successfully employed to monitor lipid motions in lipid-additive systems that included methanol, 24 proteins/peptides, 25–28 therapeutic agents 29 lipid nanodiscs, 30 and oil–water emulsions. 31 We complement the neutron scattering experiments with structural studies using small angle X-ray scattering and molecular dynamics simulations in two resolutions: all-atomistic and coarse-grained.…”
Section: Introductionmentioning
confidence: 99%